"To Whom Do the People Take Their Issues?" The Contribution of Community-Based Paralegals to Access to Justice in South Africa - Dugard, Jackie; Drage, Katherine (World Bank, Washington, DC, 2014)
Paralegals provide a crucial link to justice services and legal redress in South Africa, particularly for the rural poor. Although post-Apartheid constitutional reforms guaranteed a broad range of rights and benefits to all South Africans, including the right to legal assistance, accessing many of these benefits remains a challenge for those who live in remote areas and those who cannot afford legal representation. Community-based paralegals fill this gap by providing dispute resolution and legal support that is both geographically and financially accessible and informed by a deep understanding of the social issues and everyday challenges facing their clients. Despite the prevalence and importance of paralegals in the South African justice sector, their role remains largely under-formalized and understudied. This report seeks to address this gap by providing a broad analysis of the current state of the paralegal sector. It begins with a historical overview of paralegal services in South Africa from the apartheid period to the present. The study then maps the current state of the paralegal sector, and provides detailed information on the structure and function of key organizations that provide paralegal services. Through an analysis of twelve case studies of paralegal-assisted cases, the report identifies facilitating and hindering determinants of Community Advice Offices (CAO) functions at both the institutional and organization level.